2022
DOI: 10.1021/acs.macromol.2c00783
|View full text |Cite
|
Sign up to set email alerts
|

Selective Protein Conjugation of Poly(glycerol monomethacrylate) and Poly(polyethylene glycol methacrylate) with Tunable Topology via Reductive Amination with Multifunctional ATRP Initiators for Activity Preservation

Abstract: In this study, we compare poly­(glycerol monomethacrylate) (PGMA) of different chain lengths and architectures (linear and two-arm) with poly­(poly­(ethylene glycol) methyl ether methacrylate) (PPEGMA) as an alternative polymer platform for the synthesis of a new generation of protein–polymer conjugates. Mono- and two-arm functional atom-transfer radical polymerization (ATRP) initiators were designed and selectively attached to lysozyme at the N-terminus via reductive amination. Site-specific, grafting from ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…It was demonstrated that the growth of two polyglycerol methacrylate chains from the same protein anchoring‐site derives to a more compact macromolecular domain that provides less steric hinderance to the protein substrate entrance channel. These systems guaranteed protection against protease degradation, high stability in serum, and higher thermostability at 90 °C compared to native lysozyme [46] . Moreover, polymers with ramified structures, that is, dendronized, branched or comb‐shaped polymers, interact with the exposed residues of the proteins giving rise to a discontinuous layer that partially covers the surface of the protein.…”
Section: Tuning the Catalytic Performance And The Stability With Tail...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the growth of two polyglycerol methacrylate chains from the same protein anchoring‐site derives to a more compact macromolecular domain that provides less steric hinderance to the protein substrate entrance channel. These systems guaranteed protection against protease degradation, high stability in serum, and higher thermostability at 90 °C compared to native lysozyme [46] . Moreover, polymers with ramified structures, that is, dendronized, branched or comb‐shaped polymers, interact with the exposed residues of the proteins giving rise to a discontinuous layer that partially covers the surface of the protein.…”
Section: Tuning the Catalytic Performance And The Stability With Tail...mentioning
confidence: 99%
“…These systems guaranteed protection against protease degradation, high stability in serum, and higher thermostability at 90 °C compared to native lysozyme. [46] Moreover, polymers with ramified structures, that is, dendronized, branched or comb-shaped polymers, interact with the exposed residues of the proteins giving rise to a discontinuous layer that partially covers the surface of the protein. Therefore, the size of these gaps between polymer chains can be adjusted by engineering the size and the chemistry of the polymers.…”
Section: Effect Of the Size Position And Polymer Density On The Catal...mentioning
confidence: 99%
“…To enhance the biological activity of poly­(glycerol)–protein conjugates, an optimal combination of composition, molecular weight, and polymer architecture was crucial. , Densely grafted polymers have been studied, including the implantation of proteins in molecular bottlebrushes, the use of click chemistry to conjugate globular dendrimers, and grafting PEG macromonomers via ATRP to mask proteins . Hyperbranched polymers possess unique properties such as weak entanglement, low viscosity, and a globular conformation, making them excellent candidates for grafting from the surface of proteins .…”
Section: Introductionmentioning
confidence: 99%
“…Water stands as the most benign solvent in the ATRP of hydrophilic monomers. Although polymerization in an aqueous environment is environmentally friendly, it has limitations due to certain side reactions. These include disproportionation of Cu I activator complexes, the dissociation of the halide from higher oxidation state complexes leading to the formation of inactive species that cannot undergo deactivation, and the hydrolysis of the initiator, causing the creation of dead chains. These occurrences suggest a loss of control over the molecular weight of the final polymers.…”
Section: Introductionmentioning
confidence: 99%